Dentin tubule obturation of a bioglass-based dentin desensitizer under repeated exposure to lactid acid and brushing - Andrea S. Manz; Thomas Attin; Beatrice Sener; Philipp Sahrmann (BMC, 2019)
Abstract Background Dentin hypersensitivity is a frequent finding especially in periodontitis patients. Conventional treatment aims for obstruction of dentin tubules by disabling liquid and osmotic fluctuation to and from the pulpal chamber. A novel bioglass-based desensitizer was shown to obstruct tubules and to resist periodic exposure to lactic acid. Whether this obstruction is resistant to brushing had not been tested so far. Accordingly, the present study aimed to assess dentin tubule obstruction after repeated acid exposure and brushing. Methods Sixty dentin discs were cleaned with 17% EDTA, mounted into a pulp fluid simulator and randomly divided into 3 groups: No surface treatment in Group A, Seal&Protect® in group B and DentinoCer in group C. Discs were exposed to 0.1 M non-saturated lactic acid thrice and standardized brushing twice a day for 12 days. At baseline and after 2, 4 and 12 d samples were removed from the setting and prepared for top-view SEM analysis to assess tubule obstruction using the Olley score. Discs were then vertically cut and the section surface morphologically assessed using backscatter imaging. For both vertical and sectional surfaces EDX analysis was used to characterize the surface composition in the tubular and inter-tubular area. Results Group A showed clean tubular lumina at all time points. From day 2 onwards dentin showed exposed collagen fibers. Group 2 initially showed a complete surface coverage that flattened out during treatment without ever exposing tubules. At baseline, samples of Group C displayed a complete homogeneous coverage. From day 2 on tubules entrances with obstructed lumen became visible. While on day 4 and 12 the dentin surface exposed collagen fibers the lumina remained closed. EDX analysis of the vertical and horizontal views showed that P and Ca were predominant elements in both the inter- and tubular dentin while Si peaks were found in the tubule plugs. Conclusion While group B displayed a packed layer on the surface during the whole investigation time group C samples lost their superficial layer within 48 h. Tubule plugs containing considerable Si proportions indicated previous presence of DentinoCer, while high Ca and P proportions suggest obturation by dentin-like material.